Study guides

☆☆

Q: How do you factor this expression 3a plus ab plus 3c plus bc?

Write your answer...

Submit

Still have questions?

Related questions

0

a + 7b + 2c

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.

a(3+b)+c(3+b) * * * * * This is easy to finish: . . . = (a + c)(3 + b).

That factors to (b + 3)(a + c)

(2a + 3)(b - 3c)

55

Gathering like terms together, this is equal to 5a + 3b + 7c.

-((3c - 4)(3c + 4)(2c - 5)(2c + 5))

0.6b + 3c

It is an expression that can be simplified to: 1-4b-5c

(5c - 2)(c +1)

2ab - 6ac + 3b - 9c = 2a(b - 3c) + 3(b - 3c) = (2a + 3)(b - 3c).

2bc + 8b - 3c - 12 is an expression, not an equation or inequality. It cannot, therefore have "an answer".

It is: 3a(2b -3c) when factored

12bc - 4bd - 15xc + 5xd = 4b(3c - d) - 5x(3c - d) = (3c - d)(4b - 5x)

In other words: 3x+y=2z+a x+3y=2b+3a z+y=3c+a (all equals:) c+y=b+a

(c + 3)(c^2 - 3c + 9)

Without an equality sign the given expression remains as: 18-3c

15

(8 - 3c)(8 + 3c)

3(3c - 4)(c^2 + 2)

2ab - 6ac + 3b - 9c = b(2a + 3) - 3c(2a + 3) = (b - 3c)(2a + 3)

3c-d

4c+2 = 3c+9 4c-3c = 9-2 c = 7